Determination of Sucrose Content in Sugarcane Liquids Through Angular Dispersion Angle Measurement - Misto, M.; Mulyono, Tri; Cahyono, Bowo Eko (Jurnal ILMU DASAR, 2019)
In the sugar industry, it is important to measure the sucrose content of sugar cane so that an electronic system is needed for measurement. The system was employed an array photodiode as a sensor, red and green laser, operational amplifiers (opamp), an analog to digital converter from Arduino, and a computer. The main operation of the measurement system was conducted by the sensor and controller system in the computer. The controller was programmed with Basic program, a program that suitable for the device. The signal from array photodiode sensor is send to signal processing unit (opamp) and converted to digital signal by ADC. Then the digital code is countered by controller and displayed by monitor computer. Keywords: sugar content, array photodiode, Arduino.